Religion, culture, society: readings in the humanities and revealed knowledge. Edited by Mohammad A. Quayum and Hassan Ahmed Ibrahim. Kuala Lumpur: Silverfish Books, 2017, pp. 287. ISBN 978-983-3221-64-6. - Mohd Sobri, Mohd Helmi (IIUM Press, International Islamic University Malaysia, 2017)
This book is a collection of eleven chapters written by academics from the Kulliyyah of Islamic Revealed knowledge and Human Sciences, International Islamic University Malaysia (IIUM). As the Mohammad A. Quayum, of the editors of this book clarifi es in his introduction, the word ‘Kulliyyah’ is an Arabic term that means ‘faculty’. Titled Religion, Culture, Society: Readings in the Humanities and Revealed Knowledge, this collection consists of chapters on various political, social and religious issues. Quite a signifi cant number of chapters, fi ve out of eleven, deal with cases or issues in Malaysia, while the remaining chapters address problems or issues affecting the Muslim world in general or Muslims in specifi c countries such as India and Bangladesh. Indeed, the range of topics itself refl ects the heterogeneity of the Kulliyyah in terms of the methodological and substantive interests of its academics. Contributors of this edited work represent various departments in the Kulliyyah, including Sociology and Anthropology, Communication, History and Civilization, Political Science, Usuluddin and Comparative Religion, and English Language and Literature.